Why is C(4) photosynthesis so rare in trees? - Young, Sophie N R (J Exp Bot, 2020)
Since C(4) photosynthesis was first discovered >50 years ago, researchers have sought to understand how this complex trait evolved from the ancestral C(3) photosynthetic machinery on >60 occasions. Despite its repeated emergence across the plant kingdom, C(4) photosynthesis is notably rare in trees, with true C(4) trees only existing in Euphorbia. Here we consider aspects of the C(4) trait that could limit but not preclude the evolution of a C(4) tree, including reduced quantum yield, increased energetic demand, reduced adaptive plasticity, evolutionary constraints, and a new theory that the passive symplastic phloem loading mechanism observed in trees, combined with difficulties in maintaining sugar and water transport over a long pathlength, could make C(4) photosynthesis largely incompatible with the tree lifeform. We conclude that the transition to a tree habit within C(4) lineages as well as the emergence of C(4) photosynthesis within pre-existing trees would both face a series of challenges that together explain the global rarity of C(4) photosynthesis in trees. The C(4) trees in Euphorbia are therefore exceptional in how they have circumvented every potential barrier to the rare C(4) tree lifeform.